Exposures in Indoor Air Affecting Health - Hartiala, Maria; Elenius, Varpu; Pesquera, Alicia Aguado; Androulakis, Silas; Annesi‐Maesano, Isabella; Badyda, Artur; Brandsma, Sicco; Chatziprodromidou, Ioanna; Gajski, Goran; Garcia‐Aymerich, Judith; Giorio, Chiara; Hugg, Timo; et al. (Wiley-Blackwell, 2026)
Indoor air quality (IAQ) is influenced by a wide range of chemical, biological and physical agents that can negatively impact physical, immunological and mental health. Adverse health effects depend on the type and concentration of pollutants, duration of exposure, and individual susceptibility. The availability of data on IAQ is limited, as are standardized approaches for evaluating its health impact. This expert review aims to describe the most important indoor air determinants affecting health, and present the IDEAL cluster, which comprises seven EU-funded scientific projects on the topic of IAQ and human health. Across the IDEAL projects, knowledge is generated on exposure to a wide range of indoor air pollutants, including well-known hazards and more explorative chemical and microbiological determinants. The projects will also contribute to the implementation of low-cost and/or real-time sensors on IAQ, as well as advanced chemical and microbiological analyses, and evaluate various interventions to improve IAQ. Several of them focus on particularly vulnerable groups. Raising public awareness and implementing measures to reduce pollutant levels are essential for safeguarding health, particularly in urban areas with elevated pollution levels.